Bushen Huoxue formula protects against renal fibrosis and pyroptosis in chronic kidney disease by inhibiting ROS/NLRP3-mediated inflammasome activation - Lin Liao; Pengyu Tao; Qiming Xu; Jie Chen; Weiwei Liu; Jing Hu; Jianrao Lu (Renal Failure, 2024)
Background Renal fibrosis contributes to chronic renal failure and a decline in the quality of life. Bushen Huoxue (BSHX) formula is a Traditional Chinese Medicine used to treat chronic renal failure. However, its mechanisms of action remain unclear.Methods and results In this study, a rat model of renal fibrosis was constructed by 5/6 nephrectomy in vivo, and histopathological changes were analyzed using hematoxylin-eosin and Masson’s trichrome staining. Angiotensin II (Ang II) was used to establish an in vitro renal fibrosis cell model in vitro. Pyroptosis was measured using flow cytometry. Related markers of fibrosis and NOD-like receptor protein 3 (NLRP3) inflammasome activation were measured using western blotting and enzyme-linked immunosorbent assay. Treatment with BSHX (0.25, 0.5, and 1 g/kg) significantly inhibited renal fibrosis and damage in 5/6 nephrectomized rats and simultaneously reduced oxidative stress and NLRP3 inflammasome activation. Similarly, BSHX treatment reduced the levels of hydroxyproline, transforming growth factor-β, matrix metalloproteinase 2, and matrix metalloproteinase 9 and inactivated the Smad2/3 signaling pathway in Ang II-treated HK-2 cells. Our data also showed that treatment with BSHX reduced NLRP3 inflammasome activation and pyroptosis in Ang II-treated HK-2 cells. Moreover, fibrosis and pyroptosis in HK-2 cells induced by NLRP3 overexpression were reduced by treatment with BSHX.Conclusions BSHX significantly reduced renal fibrosis and pyroptosis, and its mechanism was mainly associated with the inhibition of reactive oxygen species (ROS)/NLRP3-mediated inflammasome activation.